CAD modelling of a milling insert - Makkai, Tamás; Sarka, Ferenc (Design of Machines and Structures, 2023)
There is often a problem when using FEM software where the tool geometry needs to be specified for the cutting simulation, one or more dimensions are not known. In the article, we present how and with what methods we determined these unknown dimensions, how we created the three-dimensional CAD model of the cutting insert as input data for the FEM software. We report our experience gained during the measurement and model creation process.